FINANCING HEIs THROUGH WAQF FUND IN BANGLADESH: ISSUES AND POSSIBILITIES - Hoque, Muhammad Nazmul (International Journal of Accounting & Finance Review, 2020)
The aim of the paper is to explicate the narrative of waqf fund for funding higher educational institutions (HEIs) in Bangladesh. nowadays, there is the reason for preventing students to pursue their higher education which is costly matters. This paper highlights some problems in implementing waqf fund for financing HEIs in Bangladesh and offer some Easier way to overcome this condition through the implementation of a waqf fund based HEIs. As a qualitative approach, data were gathered by conducting the interview from directors, academician and scholar those who have expertise on the waqf fund-based financing HEIs in Bangladesh. In addition, a review of Waqf literature is placed to examine the present status of Waqf in Bangladesh. The results show that the position of the waqf fund is essential for contributing to the society of Bangladesh and strengthening its financial stability. Taking into consideration that needs and suitable for the higher educational institutions, some problems, and possible solutions have been discussed for the country in order for a transformation in higher education facilities. At the same time, some prospects have been proposed for the country. Raising funds by collecting Hibah /donation, raising funds by different activities and promoting funds from alumni have been proposed for higher education in Bangladesh. This paper discusses the experience of waqf fund implementation in some Malaysian higher educational institutions. It also contains observations from the experience of several past universities.